The effectiveness of group cognitive-behavioral therapy on general self-efficacy, self-control, and internet addiction prevalence among medical university students - Isa Mohammadi Zeidi; Shahla Divsalar; Hadi Morshedi; Hamid Alizadeh (Wolters Kluwer Medknow Publications, 2020)
Introduction: Various studies have highlighted the high prevalence of psychological and psychiatric problems among students with Internet addiction (IA). This study aimed to determine the effect of GCBT on self-control, self-efficacy as well as the prevalence of IA amongst students of Qazvin University of Medical Sciences (QUMS). Methods: This randomized controlled trial was performed on 80 students addicted to the Internet. Participants were randomly divided into control (without intervention) and treatment group (GCBT). The experimental group participated in a GCBT program consisted of 10 two2-hour sessions based on psychosocial training, cognitive reconstruction, behavior modification, and improving emotion regulation. Data were collected using demographic information, Yang IA test, brief self-control scale, and compulsive iInternet usage scale before and 3 months after GCBT. Results: The Rfindings demonstrated significant improvements in general self-efficacy (21.90 ± 5.1--27.31 ± 3.9, F = 46.131, df = 1, P < 0.001) and self-control (33.03 ± 4.7--44.78 ± 6.1, F = 59.252, df = 1, P < 0.001), while compulsive Internet usage (41.41 ± 6.35--25.13 ± 3.97, F = 163.359, df = 1, P < 0.001) and IA (60.83 ± 9.95--36.10 ± 5.16, F = 183.302, df = 1, P < 0.001) were remarkably reduced in the experimental group after GCBT. Conclusion: This study suggests that GCBT can be an effective treatment for those college students struggling with IA, with improving the psychological variables affecting IA.